2016
DOI: 10.18869/acadpub.ijrr.14.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose awareness of radiologic technologists in major Jordanian hospitals

Abstract: Background: Radiology staff needs to jus fy the radia on exposures in order to protect themselves and others from radia on risks. The aims of this study were to examine the awareness level of radia on dose and protec on amongst radiographers and to compare their performance between major Jordanian hospitals. Materials and Methods: A cross-sec onal survey was conducted in 4 major Jordanian hospitals. A total of 85 radiographers agreed to par cipate in the study. The ques onnaire included demographic informa on,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…So, they recommended for annual assessment of their knowledge through national radiation agency. 31 Briggs-Kamara, Okoye and Omubo-Pepple, Nigeria reported that the level of awareness of radiographers is unacceptable. They concluded that concerted effort is to be made by regulatory bodies.…”
Section: Side 11mentioning
confidence: 99%
See 1 more Smart Citation
“…So, they recommended for annual assessment of their knowledge through national radiation agency. 31 Briggs-Kamara, Okoye and Omubo-Pepple, Nigeria reported that the level of awareness of radiographers is unacceptable. They concluded that concerted effort is to be made by regulatory bodies.…”
Section: Side 11mentioning
confidence: 99%
“…Thus, it is high time the radiography students are taught adequate lessons of RP with practical considerations and the curriculum should be revised accordingly highlighting the radiation protection, safety methods, radiobiology and risky issues of radiation. 31 Radiography profession is more than a job for a radiographer; it is about satisfaction and dignity as they provide proper radiation protection to the patients. It is all about making a positive impact to the life of patients with quality health service and best safety methods.…”
Section: Side 13mentioning
confidence: 99%
“…X-ray imaging is very useful in detection and diagnosis of various diseases as well as patient management [1,2]. Though it is an efficient diagnostic method, x-ray imaging constitutes a major part of human exposure to manmade radiation and hence radiation risk [3,4]. However, if the optimization principle is observed, diagnostic images can be obtained at as low as practicably achievable radiation dose [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…All these procedures utilize ionizing radiation. Therefore, it is better to use the minimum possible dose to achieve the optimum quality image of radiological imaging [2]. The international authorities such as International Council of Radiation Protection (ICRP) and national authorities such as National Council of Radiation Protection (NCRP) in India issues guidelines about the limits of radiation doses and ways to minimize radiation exposure.…”
Section: Introductionmentioning
confidence: 99%